Retrieval analysis of metal and ceramic femoral heads on a single CoCr stem design. Issue 5 (May 2017) - Di Laura, A.; Hothi, H.; Henckel, J.; Swiatkowska, I.; Liow, M. H. L.; Kwon, Y-M.; Skinner, J. A.; Hart, A. J.
Abstract : Objectives: The use of ceramic femoral heads in total hip arthroplasty (THA) has increased due to their proven low bearing wear characteristics. Ceramic femoral heads are also thought to reduce wear and corrosion at the head-stem junction with titanium (Ti) stems when compared with metal heads. We sought to evaluate taper damage of ceramic compared with metal heads when paired with cobalt chromium (CoCr) alloy stems in a single stem design. Methods: This retrieval study involved 48 total hip arthroplasties (THAs) with CoCr V40 trunnions paired with either CoCr (n = 21) or ceramic (n = 27) heads. The taper junction of all hips was evaluated for fretting/corrosion damage and volumetric material loss using a roundness-measuring machine. We used linear regression analysis to investigate taper damage differences after adjusting for potential confounding variables. Results: We measured median taper material loss rates of 0.210 mm 3 /year (0.030 to 0.448) for the metal head group and 0.084 mm 3 /year (0.059 to 0.108) for the ceramic group. The difference was not significant (p = 0.58). Moreover, no significant correlation between material loss and implant or patient factors (p > 0.05) was found. Conclusions: Metal heads did not increase taper damage on CoCr trunnions compared with ceramic heads from the same hip design. The amount of material released at the taper junctions was very low when compared with available data regarding CoCr/Ti coupling in metal-on-metal bearings. Cite this article: A. Di Laura, H. Hothi, J. Henckel, I. Swiatkowska, M. H. L. Liow, Y-M. Kwon, J. A. Skinner, A. J. Hart. Retrieval analysis of metal and ceramic femoral heads on a single CoCr stem design. Bone Joint Res 2017;6:–350. DOI: 10.1302/2046-3758.65.BJR-2016-0325.R1.